MATH SOLVE

4 months ago

Q:
# Jamal states that ax + b = a(x + c), given a, b, and c are not equal to 0.What must be the value of c for Jamal’s statement to be true?

Accepted Solution

A:

To answer the question, we must find c of the equation:

ax + b = a (x + c)

If we divide by "a" on both sides we have to:

x + b / a = x + c

For values of "a" other than zero.

So:

c = b / a.

So that the affirmation of Jamal Be true c = b / a

ax + b = a (x + c)

If we divide by "a" on both sides we have to:

x + b / a = x + c

For values of "a" other than zero.

So:

c = b / a.

So that the affirmation of Jamal Be true c = b / a